NEW PALEOMAGNETIC DATA FOR THE HAUTERIVIAN-APTIAN DEPOSITS OF THE MIDDLE VOLGA REGION: A POSSIBILITY OF GLOBAL CORRELATION AND DATING OF TIME-SHIFTING OF STRATIGRAPHIC BOUNDARIES - Guzhikov A.Yu.; Birbina A.V.; Baraboshkin E.Yu. (My University, 2003)
The aim of this project was to study the paleomagnetic stratigraphy of the Hauterivian-Aptian deposits in the Middle Volga region, namely in the areas of the Saratov, Samara, and Uliyanovsk right-hand Volga areas. Original data were obtained for the first time for the magnetic polarity of the Hauterivian and Barremian rocks of the Russian Platform. The results obtained for the Aptian rocks agree very well with the results of the previous paleomagnetic studies which had been carried out in the Uliyanovsk region earlier [Baraboshkin et al., 1999] and in the vicinities of Saratov City [Grishanov, 1984]. Based on the complex correlation of the bio- and magnetostratigraphic data for the rocks from the Middle Volga region, the North Caucasus, the North Mediterranean area, and South England, it is shown that the stage and substage boundaries of the Hauterivian, Barremian, and Aptian stages differ in terms of the absolute age from the similar boundaries in the Boreal Belt by a value of some 105 -106 years, which is comparable with the duration of the Early Cretaceous ammonite zones. The diachronism of the Lower Aptian ammonite zones (Deshayesites volgensis - D. forbesi) and of the Middle Aptian Parahoplites melchioris zone in different regions. The results of this study called for a complex substantiation and tracing of the units of the General Stratigraphic Scale (GSS). The basic GSS unit must be a stage, rather than a zone, because where boundaries were traced over a large territory, the asynchronism of the boundaries between the zones is comparable with the duration of the zones, whereas in the case of a stage it is 1-2 orders of magnitude lower. Geomagnetic inversions or isotopic data can be used to test the isochronism of stratigraphic boundaries.
Keywords: PALEOMAGNETIC DATA; GLOBAL CORRELATION; STRATIGRAPHIC BOUNDARIES; DATING; MIDDLE VOLGA REGION; Aptian; Barremian; Hauterivian; Mesozoic::Cretaceous::Lower::Aptian; Мезозой::Меловая::Нижний::Барремский; Mesozoic::Cretaceous::Lower::Barremian; Мезозой::Меловая::Нижний::Готеривский; Мезозой::Меловая::Нижний::Аптский; Mesozoic::Cretaceous::Lower::Hauterivian